Baby & Toddler Basics : Expert Answers to Parents' Top 150 Questions - Altmann, Tanya, (Tanya Remer Altmann) (Itasca, Illinois : American Academy of Pediatrics, 2023)
This easy-to-use guide helps parents with evidence-based advice for dealing with the most common issues facing babies and toddlers, including breastfeeding, baby care, developmental stages, first aid and injuries, sleep, vaccines and more.
Includes index
Keywords: Child -- Development; Child care -- Handbooks, manuals, etc; Infant -- Care